2022
DOI: 10.1002/jaoc.12111
|View full text |Cite
|
Sign up to set email alerts
|

Exploring psychological distress and impulsivity as predictors of undergraduate problematic alcohol use

Abstract: The goal of this research was to explore psychological distress (i.e., depression, anxiety, and stress) and impulsivity as predictors of problematic alcohol use (PAU) among 481 undergraduate college students between the ages of 18 and 25. The results showed that only impulsivity was predictive of PAU. Controlling for other factors in the model, for every one-unit increase in impulsivity score, the odds were 2.3 times greater that participants would engage in PAU. Implications for counselors and stakeholders ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…This is similar to the other international studies that have used the same BIS-Brief scale. The mean score was lower than the mean score of 19.03 found in a study in the USA [11]. However, this is expected as the USA study was conducted among young adults aged 18-25 years.…”
Section: Discussioncontrasting
confidence: 72%
“…This is similar to the other international studies that have used the same BIS-Brief scale. The mean score was lower than the mean score of 19.03 found in a study in the USA [11]. However, this is expected as the USA study was conducted among young adults aged 18-25 years.…”
Section: Discussioncontrasting
confidence: 72%
“…Evidence attests to the co-occurrence of excessive alcohol use and psychological distress. People with depression and anxiety might use alcohol to help ease symptoms, but excessive alcohol use can also worsen their mental health [39][40][41]. However, there is no consistent pattern for how excessive alcohol use and psychological distress interact to influence each other.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of alcohol or drug use among university students is also due to the substantial changes occurring in their lives, including social factors, peer, teachers, or parent's pressure ( 18 ). A cross-sectional study of university students in Nigeria showed that nearly 4.2% were dependent on alcohol, while 14.1% had “low-risk use” for other psychoactive substances ( 19 ).…”
Section: Introductionmentioning
confidence: 99%